Benthic biology in the Polish exploration contract area of the Mid-Atlantic Ridge: The knowns and the unknowns. A review - Radziejewska, Teresa; Błażewicz, Magdalena; Włodarska-Kowalczuk, Maria; Jóźwiak, Piotr; Pabis, Krzysztof; Węsławski, Jan Marcin (Frontiers in Marine Science, 2022)
In February 2018, the Government of Poland and the International Seabed Authority signed a 15-year contract for exploration of polymetallic sulfide deposits on a section of the Mid-Atlantic Ridge extending between the Hayes, Atlantic and Kane transform faults (32°45.378’ N, 39°57.760’ W to 26°14.411’ N, 44°18.008’ W). The contractor is obliged to collect data on the contract area environment and its ecosystem components. In this context, it is important that the contractor establishes a sound starting point which further baseline investigations can be referred to. Such a starting point involves assessment of currently held information and, most importantly, knowledge gaps on the ecosystem components in the area of exploration (and of potential future exploitation). Of major importance here is the knowledge on benthic communities, as it is the benthos that will be most affected by any human intervention in the area of interest. Based on available published evidence, we have reviewed the present state of knowledge on benthic communities in the Polish exploration contract area (PECA). In the process, we have identified important knowledge gaps that will need to be addressed during exploration surveys. These include, but are not limited to, the distribution and structure of benthic communities throughout the contract area, the spatial and temporal variability of those communities, possible differences between communities inhabiting active and inactive vent fields, connectivity issues and the recovery potential. Special consideration should be given to Lost City, a geologically and ecologically unique hydrothermal field which has been a focus of international research and an important conservation target.